Two-stage multiobjective optimization of maintenance scheduling for pavements - Denysiuk, Roman (2017)
Pavements heavily influence the management costs in highway networks. Operating pavements represents a challenging task 6 involving complex decisions on the application of maintenance actions to keep them at a reasonable level of performance. The major diffi- 7 culty in applying computational tools to support decision making lies in a large number of pavement sections as a result of a high length of 8 road networks. This paper addresses maintenance scheduling for pavements by consolidating this task into two stages. In each stage, multi- 9 objective optimization is used to optimize maintenance schedules. The main motivation is to obtain a computationally treatable model for 10 large road networks. The first stage is defined by a collection of pavement sections composing the road network. In this stage, the performance 11 and maintenance models are addressed. These models account for uncertainties in the future performance and effects of maintenance by 12 defining model parameters as random variables. The second stage refers to combining maintenance schedules for individual sections to 13 determine the optimal maintenance plan at the network level. The results obtained for the real road network demonstrate the validity 14 and usefulness of the proposed framework. Moreover, this framework is general and can be extended to different types of infrastructure 15 assets.